Improving inpatient warfarin therapy safety using a pharmacist-managed protocol. Issue 2 (20th April 2018) - Daniels, Paul R; Manning, Dennis M; Moriarty, James P; Bingener-Casey, Juliane; Ou, Narith N; O'Meara, John G; Roellinger, Daniel L; Naessens, James M
Abstract : Introduction: Safe management of warfarin in the inpatient setting can be challenging. At the Mayo Clinic hospitals in Rochester, Minnesota, we set out to improve the safety of warfarin management among surgical and non-surgical inpatients. Methods: A multidisciplinary team designed a pharmacist-managed warfarin protocol (PMWP) which designated warfarin dosing to inpatient pharmacists with guidance from computerised dosing algorithms. Ordering this protocol was ultimately designed as an 'opt out' practice. The primary improvement measure was frequency of international normalised ratio (INR) greater than 5; secondary measures included adoption rate of the protocol, a counterbalance INR metric (INR <1.7 three days after first inpatient warfarin dose), and complication rates, including bleeding and thrombosis events. An interrupted time series analysis was conducted to compare outcomes. Results: Among over 50 000 inpatient warfarin recipients, the PMWP was adopted for the majority of both surgical and non-surgical inpatients during the study period (1 January 2005 to 31 December 2011). The primary improvement measure decreased from 5.6% to 3.4% for medical patients and from 5.2% to 2.4% for surgical patients during the preimplementation and postimplementation periods, respectively. The INR counterbalance measure did not change. Postoperative bleeding decreased from 13.5% to 11.1% among surgical patients, but bleeding was unchanged among medical patients. Conclusion: Our PMWP led to achievement of improved INR control for inpatient warfarin recipients and to less near-term bleeding among higher risk, surgical patients.